Pulmonary vein isolation using ablation index vs. CLOSE protocol with a surround flow ablation catheter. Issue 1 (13th September 2019) - Berte, Benjamin; Hilfiker, Gabriella; Moccetti, Federico; Schefer, Thomas; Weberndörfer, Vanessa; Cuculi, Florim; Toggweiler, Stefan; Ruschitzka, Frank; Kobza, Richard
Abstract: Aims: Pulmonary vein isolation (PVI) using ablation index (AI) incorporates stability, contact force (CF), time, and power. The CLOSE protocol combines AI and ≤6 mm interlesion distance. Safety concerns are raised about surround flow ablation catheters (STSF). To compare safety and effectiveness of an atrial fibrillation (AF) ablation strategy using AI vs. CLOSE protocol using STSF. Methods and results: First cluster was treated using AI and second cluster using CLOSE. Procedural data, safety, and recurrence of any atrial tachycardia (AT) or AF >30 s were collected prospectively. All Classes 1c and III anti-arrhythmic drugs (AAD) were stopped after the blanking period. In total, all 215 consecutive patients [AI: 121 (paroxysmal: n  = 97), CLOSE: n  = 94 (paroxysmal: n  = 74)] were included. Pulmonary vein isolation was reached in all in similar procedure duration (CLOSE: 107 ± 25 vs. AI: 102 ± 24 min; P  = 0.1) and similar radiofrequency time (CLOSE: 36 ± 11 vs. AI: 37 ± 8 min; P  = 0.4) but first pass isolation was higher in CLOSE vs. AI [left veins: 90% vs. 80%; P  < 0.05 and right veins: 84% vs. 73%; P  < 0.05]. Twelve-month off-AAD freedom of AF/AT was higher in CLOSE vs. AI [79% (paroxysmal: 85%) vs. 64% (paroxysmal: 68%); P  < 0.05]. Only four patients (2%) without recurrence were on AAD during follow-up. Major complications were similar (CLOSE: 2.1% vs. AI: 2.5%; P  = 0.87). Conclusion: The CLOSE protocol is more effective than a PVI approach solely using AI, especially in paroxysmal AF. In this off-AAD study, 79% of patients were free from AF/AT during 12-month follow-up. The STSF catheter appears to be safe using conventional CLOSE targets.